1976
DOI: 10.1002/cber.19761090816
|View full text |Cite
|
Sign up to set email alerts
|

Oxa‐bis‐ und Oxa‐tris‐σ/π‐homobenzole Synthesen und σ → π‐Isomerisierungen

Abstract: Oxa-bis-and Oxa-tris-u/n-homobenzenes Syntheses and a + n-IsomerhitionsAddition of diazomethane to the benzene oxides 13a-d yields -under the cis-directing influence of the oxirane oxygen atom often stereoselcciively -the cis-mono- (16% c, d), the cis-bis-(17a-c) and the rr.utis-bis-l-pyrazolines 19b. Photolysis of 16a.c.d. of 17b.c. and of 19b proceeds exclusively to the oxa-bis-a-homohenzenes 20a, c, d and the cislrrans-oxa-tris-a-homobenzenes 24b, c and 30b, respectively. In the case of the diester 17a form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1978
1978
2011
2011

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(4 citation statements)
references
References 81 publications
0
4
0
Order By: Relevance
“…After warming to room temperature the solvent was evaporated in in vacuo. Recrystallization of the residue from hexane gave 7.59 g (76%) of 6 as colorless needles: mp 82-83°C; ir (KBr pellet) v, , : 1466(KBr pellet) v, , : , 1384(KBr pellet) v, , : , 1322(KBr pellet) v, , : , 1167 6.8,7.7,9.1Hz),2.90(IH,dd,J=4.5,15.4Hz),2.69(1H,dd,J= 6.8,16.1Hz),2.61(1H,dd,J = 7.7,16.1 Hz),2.29(1H,dd,J = 8.3,15.4Hz),1.34(3H,s), and 1.32 (3H, s); I3C nmr 6: 61.9 and 61.0 (oxirane carbons), 50.5 and 49.6(2 X CHBr), 40.8 and39.9(2 X CH2), 19.9and 19.5 (2 X CH3); ms m/z (%): 205 (1 l), 203 (12), 165 (I), 163 (I), 123 (20), 95 (7), 81 (17), 79 ( l l ) , and 43 (100).…”
Section: X-ray Structure Determination Ofmentioning
confidence: 99%
See 1 more Smart Citation
“…After warming to room temperature the solvent was evaporated in in vacuo. Recrystallization of the residue from hexane gave 7.59 g (76%) of 6 as colorless needles: mp 82-83°C; ir (KBr pellet) v, , : 1466(KBr pellet) v, , : , 1384(KBr pellet) v, , : , 1322(KBr pellet) v, , : , 1167 6.8,7.7,9.1Hz),2.90(IH,dd,J=4.5,15.4Hz),2.69(1H,dd,J= 6.8,16.1Hz),2.61(1H,dd,J = 7.7,16.1 Hz),2.29(1H,dd,J = 8.3,15.4Hz),1.34(3H,s), and 1.32 (3H, s); I3C nmr 6: 61.9 and 61.0 (oxirane carbons), 50.5 and 49.6(2 X CHBr), 40.8 and39.9(2 X CH2), 19.9and 19.5 (2 X CH3); ms m/z (%): 205 (1 l), 203 (12), 165 (I), 163 (I), 123 (20), 95 (7), 81 (17), 79 ( l l ) , and 43 (100).…”
Section: X-ray Structure Determination Ofmentioning
confidence: 99%
“…Similarly, adducts derived from 1,2,4-triazoline-3,s-dione dienophiles have been reported as the products of anti addition (IS), but this assignment of stereochemistry was based on one structure that was determined by X-ray crystallography (16). In contrast, on acetone-sensitized excitation, diazomethane added to the face of a benzene oxide syn to the oxygen (17). We report here the Diels-Alder cycloadditions of three benzene oxides with carbon dienophiles, and the first irrefutable proof for the stereochemistry of the products.…”
Section: Introductionmentioning
confidence: 99%
“…Early studies based on X-ray analysis discarded the azepine-benzeneimine equilibrium (Scheme 21.4) for simple 1H-azepines in the solid state, and 1 H NMR data obtained at different temperatures were also consistent with the azepine structure [58]. However, other NMR studies [88] 84] demonstrated the existence of the azepine-benzeneimine equilibrium in densely substituted 1H-azepines such as 72, where the bicyclic isomer 73 is present at a level of 3-10% in the equilibrium mixture (Scheme 21.5). Further theoretical studies (MINDO/3) showed that the benzeneimine is a nonplanar bicycle in which the aziridine ring is 72.6 out of the plane of the six-membered ring.…”
Section: Valence Tautomerism In Seven-membered Heterocyclesmentioning
confidence: 77%
“…The principal steps in these elaborate preparations were the stereoselective ring opening of 297 with the weakly basic mixed cyanocuprate of lithiated tris(isopropylsilyl)-protected propyne and fixation of the all-axial orientation of the six substituents on the flexible cyclohexane precursor 298 by bridging the three hydroxy groups in the form of the adamantoid orthophosphates 299 − 301 (Scheme ) . Successful application of this strategy led to the preparation of cis -tris-σ-homobenzenes 302 -iPr, 302 -Me, 304 , and 306 in 15%, 13%, 11%, and 2.5% overall yield, respectively …”
Section: 3 Fused Systemsmentioning
confidence: 99%